Traffic Light Signal System Using Radar-Based Target Detection and Tracking - Munjal, Manish; Grewal, Amit; Gogna, Karan (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
A novel system and method of integrating an RF emissions device, such as aradar system (103A), within a traffic control indicator (101) system. The system and method determines, using LFM-CW radar signals (201) and a multistage spectral processing algorithm (600), if one or more object/vehicle targets will enter an intersection and comprises receiving a radar echo response (203) indicating the object/vehicle target (104) is approaching the intersection, receiving range and velocity of the object/vehicle targets (104), and based on the receiving, determining if the object/vehicle target (104) will enter the intersection. The system and method can programmatically be configured to activate red-light-hold, green-light-extension, or left-turnwarning.